Long Term Diversity and Distribution of Non-photosynthetic Cyanobacteria in Peri-Alpine Lakes - Monchamp, Marie-Eve; Spaak, Piet; Pomati, Francesco (Frontiers in Microbiology, 2019)
The phylum Cyanobacteria comprises a non-photosynthetic lineage. The diversity and distribution of non-photosynthetic cyanobacteria (NCY) across aquatic environments are currently unknown, including their ecology. Here, we report about composition and phylogenetic diversity of two clades of NCY in ten lakes of the European peri-Alpine region, over the past ~100 years. Using 16S rDNA sequences obtained from dated sediment cores, we found almost equal proportion of taxa assigned to Melainabacteria and the deepest-branching group Sericytochromatia (ML635J-21) (63 total detected taxa). The topology of our reconstructed phylogenies reflected evolutionary relationships expected from previous work, that is, a clear separation between the deepest branching Sericytochromatia, the Melainabacteria, and the photosynthetic cyanobacteria clades. While different lakes harbored distinct NCY communities, the diversity of NCY assemblages within and between lakes (alpha and beta diversity) did not significantly change over the last century. This is in contrast with what was previously reported for photosynthetic cyanobacteria. Unchanged community phylogenetic similarity over geographic distance indicated no dispersal limitation of NCY at the regional scale. Our results solicit studies linking in-lake environmental factors to the composition of these microorganisms’ communities, whose assembly appeared not to have been influenced by large-scale anthropogenic environmental changes. This is the first attempt to study the diversity and distribution of NCY taxa across temperate lakes. It provides a first step towards understanding their distribution and ecological function in pelagic aquatic habitats, where these organisms seem to be prevalent.